2016
DOI: 10.1016/j.jid.2016.06.610
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of SOX2 Underlies the Inhibitory Effects of the Triphenylmethane Gentian Violet on Melanoma Cell Self-Renewal and Survival

Abstract: Human melanomas contain a population of tumor-initiating cells that are able to maintain the growth of the tumor. We previously showed that the embryonic transcription factor SOX2 is essential for self-renewal and tumorigenicity of human melanoma-initiating cells. However, targeting a transcription factor is still challenging. Gentian violet (GV) is a cationic triphenylmethane dye with potent antifungal and antibacterial activity. Recently, a combination therapy of imiquimod and GV has shown an inhibitory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…Our results are in agreement with a recent study showing the higher expression of STAT3 in a population of tumor‐initiating cells in murine melanomas (Wang et al, ) characterized by the increased expression of four stemness factors ( Oct4 , Sox2, Klf4 , and c‐Myc ). Other studies exploring the plasticity of human melanoma cells confirm our findings (Ohanna et al, ; Pietrobono et al, ; Wang et al, ). Secretome of senescent melanoma cells increased the abundance of melanoma CSCs with elevated STAT3 activation and signaling (Ohanna et al, ).…”
Section: Disscusionsupporting
confidence: 91%
“…Our results are in agreement with a recent study showing the higher expression of STAT3 in a population of tumor‐initiating cells in murine melanomas (Wang et al, ) characterized by the increased expression of four stemness factors ( Oct4 , Sox2, Klf4 , and c‐Myc ). Other studies exploring the plasticity of human melanoma cells confirm our findings (Ohanna et al, ; Pietrobono et al, ; Wang et al, ). Secretome of senescent melanoma cells increased the abundance of melanoma CSCs with elevated STAT3 activation and signaling (Ohanna et al, ).…”
Section: Disscusionsupporting
confidence: 91%
“…Likewise, in A375 SOX2 OE cells that showed strong STAT3 activation the PP2 treatment did not alter this status. 35 The authors suggested that GV suppressed STAT3 activation through an EGFRdependent mechanism. Interestingly, in SK Mel 28 cells the OE of CD24 leads to the activation of Src but not of STAT3 ( Supporting Information, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could observe an upregulation of STAT3 already after 6 hr of vem treatment while Src was only activated after 96 hr of vem treatment (data not shown). 35 Thus, it is quite possible that diverse signalling pathways can lead to STAT3 activation which in turn can trigger SOX2 expression. 4g).…”
Section: Discussionmentioning
confidence: 99%
“…We also propose the following biomarkers to assess the sequence of events in gentian violet‐mediated tumor regression. Sox2 is one of the Yamanaka factors in tumor stem cells, and we have recently demonstrated that gentian violet downregulates Sox2 . Immunohistochemistry for Sox2 could be performed in vivo in lymphomas treated with gentian violet.…”
mentioning
confidence: 99%